An exploratory pilot of factors associated with premenstrual syndrome in minority women - Mallory Perry; Michelle Judge; Danielle Millar; Deborah McDonald (Elsevier, 2015)
Purpose: This investigation explored factors associated with premenstrual syndrome (PMS) in minority women, and compared the response of minority and non-minority women supplemented with omega-3 fatty acids (FA) in the form of fish oil. Methods: This descriptive, correlational, retrospective pilot was a secondary data analysis. Participants consuming 2 g of fish oil/d (n = 15) in the larger study were included. The Moos Menstrual Distress Questionnaire (MMDQ) was assessed monthly for two months to acquire a mean baseline MMDQ score. The total sample was stratified to evaluate racial variations in PMS symptoms (non-minority, n = 7; minority, n = 8). MMDQ score at 5 months was compared to the mean baseline score within each group. Results: Fish oil supplementation significantly reduced PMS symptoms in both groups (non-minority p = 0.002; minority p = 0.046) with a large effect of 1.4 for both groups. Mean MMDQ total scores were not significantly different between groups at 5 months. Conclusions: This pilot evidence of improved PMS symptoms in minority and non-minority groups related to fish oil supplementation supports a universal treatment approach and highlights need for a larger-scale investigation.